Evaluation of cartridge-based nucleic acid amplification test for diagnosis of tuberculosis in children in various body fluids - Agarwal, Dipti; Bhatia, Rakesh; Dayal, Rajeshwar; Khera, Rhythm; Narayan, Shamrendra; Goyal, Ankur (Indian Journal of Child Health, 2019)
Introduction: The paucibacillary nature presents a major challenge in the diagnosis of tuberculosis (TB) in children. The utilization of cartridge-based nucleic acid amplification test (CBNAAT) for the diagnosis of TB presents itself with added advantages such as detection to resistance to rifampicin and short turnaround time. Objectives: The aim of the study is to evaluate the diagnostic yield of CBNAAT in various body fluids and to compare with BACTEC-MGIT 960 and acid-fast bacilli (AFB) microscopy in children with suspected TB and to see the prevalence of rifampicin resistance in the study population using CBNAAT. Materials and Methods: This cross-sectional study included participants